2017
DOI: 10.12973/eu-jer.6.4.495
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Concepts and Subjects in Biology Perceived to be Difficult to Learn and Teach by the Pre-Service Teachers Registered in the Pedagogical Formation Program

Abstract: This study examines the subjects and concepts in biology perceived to be difficult to learn and teach by 759 pre-service biology teachers registered in the pedagogical formation program at Uludag University Faculty of Education in the academic year of 2005-2016, as well as the associations that word "biology" first calls to their mind. The study was designed as a survey model, and a questionnaire of three scaled questions was used as a data collection tool. The data were classified into 10 different categories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
0
11
0
6
Order By: Relevance
“…The result of a study conducted by Çimer (2012) showed that Turkish students were difficult to learn material cycle, endocrine system, aerobic respiration, cell division, gene and chromosome. The other result of the study that was also conducted in Turkey revealed that physiology, genetics and cytology were categorized as difficult Biology topics (Gungor & Ozkan, 2017). In a similar direction, the study carried out by Etobro & Fabinu (2017) also informed that Nigerian students experienced difficulty in learning some topics of Biology subject.…”
Section: Introductionmentioning
confidence: 88%
“…The result of a study conducted by Çimer (2012) showed that Turkish students were difficult to learn material cycle, endocrine system, aerobic respiration, cell division, gene and chromosome. The other result of the study that was also conducted in Turkey revealed that physiology, genetics and cytology were categorized as difficult Biology topics (Gungor & Ozkan, 2017). In a similar direction, the study carried out by Etobro & Fabinu (2017) also informed that Nigerian students experienced difficulty in learning some topics of Biology subject.…”
Section: Introductionmentioning
confidence: 88%
“…Understanding of scientific processes is one of the most important aims of teaching science (Al-Doulat, 2017). Present literature on learning concepts concentrates on a two-phase theory: the formation of conceptual knowledge and the development of procedural knowledge (Tennyson & Cocchiarella, 1986 numerous students have difficulty acquiring them (Chandrasekaran, Silamboli, Gunasekaran, & Sujathamalini, 2020;Gungor & Ozkan, 2017). Study findings have demonstrated that students have difficulty understanding basic concepts of physics, such as the concepts of force and displacement (Erfan & Ratu, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Disiplin membantu siswa dalam proses pembentukan sikap, prilaku dan akan mengantar seorang siswa sukses dalam belajar dan ketika bekerja nanti. "Therefore, the discipline is developing and prospering each passing day" (Gungor & Ozkan, 2017). Fungsi kedisiplinan antara lain, yaitu: menata kehidupan bersama, disiplin berguna untuk menyadarkan seseorang bahwa dirinya perlu menghargai dengan cara mentaati dan mematuhi peraturan yang berlaku (Tu'u, 2004).…”
Section: Strategi Pembelajaran Tugas Dan Paksaunclassified